„Trafieni”. AIDS w polskiej literaturze najnowszej (na wybranych przykładach) - Winnicka, Katarzyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
The first case of HIV in Poland was discovered in the mid-1980s. Infected and sick people had their windows broken at that time. Over the years aggression has been replaced with tolerance, and the situation of HIV-positive individuals has changed as well. Falling sick is not tantamount to a death sentence and infected people can grow old. Nevertheless, one of the main problems such people face is a fear of loneliness, not to mention lack of friendliness and understanding from doctors and people professionally connected with this problem. On the basis of the analysis of the short stories "Józef H." written by Marek Kochan and "Trafieni" written by Michał Witkowski we present the way HIV is described in literature as well as focus on the language employed to describe this disease. Additionally, we take into consideration comments on the social context of HIV/AIDS in Poland.
Infected. AIDS in contemporary Polish literature (on selected examples)
Keywords: Kochan, Marek; Witkowski, Michał; choroba; tolerancja; disease; tolerance